A Unique Transition to the Democratic Constitutional Monarchy in Bhutan - Udomariyasap, Bulanchine (Political Science Critique, 2025)
Bhutan’s transition to a constitutional monarchy in 2008 marks it as the second country in the world, after Denmark, to have undergone such a peaceful transformation without violence or bloodshed. Over a span of more than two decades and through four general elections, Bhutan can be said to have successfully established a new political system. Importantly, this transition carries several distinctive characteristics, making it truly unique, unlike any other political transformation in the world. This transition cannot be fully explained by any existing theory of political transition synthesized by scholars, whether focused on structural factors or agency, particularly regarding the role of political crisis or conflict. Instead, Bhutan’s transition was initiated and persistently driven by the monarchy itself. This began in 1953 during the reign of King Jigme Dorji Wangchuck, the third king of the Wangchuck Dynasty. and represents a carefully planned and gradual path toward a democratic system with the monarch as head of state. The Fourth King played a pivotal role by initiating the constitutional drafting process in 2001, which culminated in the adoption of the Constitution in 2008, marking the centenary of the Wangchuck dynasty, and coinciding with the ascension of the Fifth King, Jigme Khesar Namgyel Wangchuck, the current monarch. In the interim, the Fourth King formally abdicated in 2005 at the age of only 51, while the Crown Prince was only 28. Additionally, a royal decree was issued mandating that Bhutanese monarchs must abdicate upon reaching the age of 65, as later codified in Article 6 of the Constitution of the Kingdom of Bhutan. This phenomenon thus opens up new frontiers in political science knowledge, particularly in the design of political and administrative structures under a democratic constitutional monarchy. It calls for further comparative research on royal abdication and hereditary succession in constitutional monarchies. powers and checks and balances to prevent the abuse of authority. Also, the English "commercial republic" is grounded on the realistic idea of human nature, allowing individuals to pursue wealth and status while ensuring political freedom within a well-structured government. Within the framework of the English commercial modern republic, the regulation of individual desires is conceived not as a suppression of state liberty but as a rational calibration aimed at preserving the common good. Such a polity aspires to reconcile the tension between personal autonomy and collective stability by instituting a non-extremist, well-ordered form of government that safeguards both political and economic freedoms.